Biomechanical analysis of skilled female gymnasts` technique in «round-off, flic-flac» type on the vault table - Kashuba, V.; Khmelnitskaya, I.; Krupenya, S. (Journal of Physical Education and Sport, 2012)
It is important to know the biomechanical characteristics of technique for skilled female gymnasts performing vault group «Round-off, flic-flac» on «vault table». The vaults of 20 skilled female gymnasts - the members of Ukraine`s National Team - were filmed using Sony Handicam DCR-VX2100E digital camera (25 frames per second) positioned in line with the table, perpendicular to the direction of the runway. We determined the leading elements of the vault movement structure. There are the biomechanical characteristics of the post-flight phase: time in air, height off the table, horizontal distance from the table, which was confirmed by correlation analysis. Grounding on the results of biomechanical analysis we have developed the training program for skilled female gymnasts in order to improve their «Round-off, flic-flac» vault performance. 20 qualified female gymnasts were divided by random selection into two groups of 10 gymnasts both in control and experimental group. Gymnasts in both groups had no statistically significant differences by biomechanical characteristics of vault technique at the beginning of the pedagogical experiment. Pedagogical experiment was carried out during 12 months at the training to main starting in the Ukrainian and World Championships. Gymnasts in both groups trained on a single plan per 3 hours twice a day, six days a week. Gymnasts performed vaults for 45 minutes as in the experimental and the control group during each training session. The only difference between the groups was that the control group trained under the traditional program and the experimental group trained by our program. The effectiveness of developed program was confirmed by pedagogical experiment. Gymnasts of the experimental group increased «Round-off, flic-flac» vault scores statistically significantly (p <0.05); gymnasts in the control group increased their scores insignificantly (p> 0.05).